The lncRNA H19/miR-766-3p/S1PR3 Axis Contributes to the Hyperproliferation of Keratinocytes and Skin Inflammation in Psoriasis via the AKT/mTOR Pathway - Yuexi He; Xiran Yin; Jianjun Yan; Xue Li; Qing Sun (Hindawi Limited, 2021)
Background. The pathogenesis of long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) are well studied in psoriasis. However, little is known about how specific lncRNAs and miRNAs affect the mechanism of psoriasis development and which pathways are involved. Objectives. To explore the role of the lncRNA H19/miR-766-3p/S1PR3 axis in psoriasis. Methods. miRNA and lncRNA microarrays were performed using IL-22-induced HaCaT cells and psoriatic lesions, respectively. Fluorescence in situ hybridization and quantitative reverse-transcriptase polymerase chain reaction were used to detect the expression of miR-766-3p and lncRNA H19. Luciferase reporter assays were used to identify miR-766-3p/lncRNA H19 and miR-766-3p/S1PR3 combinations. CCK-8 and ELISA were performed to evaluate the proliferation of keratinocytes and the secretion of pro-inflammatory cytokines. Western blot analysis was used to detect the expression of S1PR3 and its downstream effector proteins. Results. MiR-766-3p was upregulated in both HaCaT cells treated with the psoriasis-related cytokine pool (IL-17A, IL-22, IL-1 alpha, oncostatin M, and TNF-alpha) and tissues. Overexpression of miR-766-3p promoted keratinocyte proliferation and IL-17A and IL-22 secretion. LncRNA H19 and S1PR3 were demonstrably combined with miR-766-3p by luciferase reporter assay. lncRNA H19 repressed proliferation and inflammation, which were reduced by the miR-766-3p. AKT/mTOR pathway effected proliferation and inflammation by the lncRNA H19/miR-766-3p/S1PR3 axis. Conclusions. We established that downregulation of lncRNA H19 promoted the proliferation of keratinocytes and skin inflammation by up-regulating miR-766-3p expression levels and inhibiting activation of S1PR3 through the AKT/mTOR pathway in psoriasis.